2017
DOI: 10.1159/000477608
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Sodium Sensitivity and Eryptosis in Chronic Hemodialysis Patients

Abstract: Background/Aims: In hemodialysis (HD) patients the endothelial and erythrocyte glycocalyx is impaired which in turn correlates with elevated erythrocyte sodium sensitivity (ESS). Additionally, apoptotic erythrocyte death (eryptosis), characterized by phosphatidylserine (PS) exposure on the cell surface, is increased in this population. We aimed to explore the relationship of ESS and eryptosis. Methods: Blood samples were collected from 11 healthy controls and 20 chronic HD patients before and after midweek HD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
5
1
Order By: Relevance
“…ESA in HD and 4583 I.U. ESA in PD), remained anemic with hemoglobin levels of 10.07 g·dL −1 (HD) and 10.89 g·dL −1 (PD), indicating that anemia is a major complication in CKD . Mounting evidence for a decreased erythrocyte survival in CKD is provided by additional studies .…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 96%
“…ESA in HD and 4583 I.U. ESA in PD), remained anemic with hemoglobin levels of 10.07 g·dL −1 (HD) and 10.89 g·dL −1 (PD), indicating that anemia is a major complication in CKD . Mounting evidence for a decreased erythrocyte survival in CKD is provided by additional studies .…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 96%
“…Accordingly, similar changes in the RBC phenotype of DM patients can be surmised in concomitant conditions such as hypertension and patients with dyslipidemia [ 109 , 125 , 126 ]. Chronic renal failure can aggravate RBC cell death in DM, as uremia and proteinuria have been shown to reduce RBC survival in multiple studies [ 64 , 127 , 128 , 129 , 130 , 131 , 132 ]. Dialysis treatment may further impact RBC survival within DM patients [ 130 , 133 , 134 ].…”
Section: Multifactorial Mechanisms Explaining Shortened Rbc Lifespan ...mentioning
confidence: 99%
“…Chronic renal failure can aggravate RBC cell death in DM, as uremia and proteinuria have been shown to reduce RBC survival in multiple studies [ 64 , 127 , 128 , 129 , 130 , 131 , 132 ]. Dialysis treatment may further impact RBC survival within DM patients [ 130 , 133 , 134 ]. In a previous study, chronic kidney disease was shown to enhance oxidative imbalance and PS exposure in RBCs drawn from T2D patients [ 135 ].…”
Section: Multifactorial Mechanisms Explaining Shortened Rbc Lifespan ...mentioning
confidence: 99%
“…The question whether the HD therapy ameliorates or triggers eryptosis remains controversial. Results suggesting both an increase (Abed et al, 2014) and a reduction (Meyring-Wösten et al, 2017) of PS exposure post HD session were reported.…”
Section: Eryptosis Pathways: Overviewmentioning
confidence: 93%